1991
DOI: 10.1152/ajprenal.1991.260.4.f562
|View full text |Cite
|
Sign up to set email alerts
|

ANF-mediated renal cGMP generation in congestive heart failure

Abstract: Previous studies have demonstrated that the biological actions of atrial natriuretic factor (ANF) are mediated via increases in its intracellular second messenger guanosine 3',5'-cyclic monophosphate (cGMP). Because cGMP egresses rapidly from target cells after ANF binding to particulate guanylate cyclase-linked receptors, extracellular cGMP may be a useful biological marker for the action of ANF in vivo under pathophysiological conditions. The present studies tested the hypothesis that the avid sodium retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 0 publications
4
44
1
Order By: Relevance
“…One possible explanation is that the renin angiotensin aldosterone system activation in CHF is impairing cGMP generation in congestive heart failure. In fact, a recent study (13) demonstrates that despite steadily increasing plasma ANF concentrations, plasma cGMP levels plateau during the evolution of experimental heart failure in association with progressive increases in plasma renin activity. Moreover, an elegant in vitro study by Smith and Lincoln (30) demonstrates that angiotensin II mediated increases in intracellular phophodiesterases may impair ANF mediated increases in cyclic GMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that the renin angiotensin aldosterone system activation in CHF is impairing cGMP generation in congestive heart failure. In fact, a recent study (13) demonstrates that despite steadily increasing plasma ANF concentrations, plasma cGMP levels plateau during the evolution of experimental heart failure in association with progressive increases in plasma renin activity. Moreover, an elegant in vitro study by Smith and Lincoln (30) demonstrates that angiotensin II mediated increases in intracellular phophodiesterases may impair ANF mediated increases in cyclic GMP.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies (2-7) have demonstrated a blunted renal response to exogenous ANF in CHF. Multiple mechanisms have been implicated in this blunted renal response to ANF in CHF including: changes in ANF receptor density (8)(9)(10), enhanced degradation and clearance of ANF (11,12), altered postreceptor signal transduction (13), activation ofcounterregulatory neurohumoral systems (14,15), and decreased renal perfusion pressure (5). These mechanisms are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that both the NP/cGMP and NO/cGMP signaling pathways are impaired in overt CHF and that such impairment may contribute to the progression of cardiorenal dysfunction in CHF (2,5). With regard to the kidney, we previously reported, as have others, that the glomerular, natriuretic, and urinary cGMP excretory responses to both atrial natriuretic peptide and brain NP (BNP) are attenuated in overt experimental and human CHF (6,7). In addition, Nesiritide, the recombinant human BNP (Scios, Inc., Fremont, CA) that is approved for the management of acute decompensated CHF, in some clinical studies failed to demonstrate a renal-enhancing property (8,9).…”
mentioning
confidence: 90%
“…After centrifugation at 2,500 rpm at 4°C for 10 min, plasma was separated and stored at Ϫ20°C until assay. Plasma levels of ANP, cGMP, and plasma renin activity were determined by radioimmunoassay (7,29). Plasma and urine concentrations for electrolytes and lithium were determined by flame photometer (model 1L943; Instrumentation Lab, Lexington, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Infusion of these three NPs in animals and humans results in natriuresis and diuresis and, at certain doses, an increase in glomerular filtration rate (GFR; 9, 10, 23). It should be noted that in severe experimental or human heart failure, a renal hyporesponsiveness may occur to the NP system (NPS) with excessive hypotension linked to worsening renal function (29,37,42). The importance of the NPS and the NPR-A in renal regulation is underscored by studies of genetic and pharmacologic receptor disruption characterized by impaired renal sodium handling and often hypertension (5,12,24,34).…”
mentioning
confidence: 99%